Survey of the Physico-chemical and Parasitological Quality of the Wastewaters Used in Irrigation (Souk Ahras, North-East of Algeria) - Mamine, N; Khaldi, F; Grara, N. (My University, 2020)
The reuse of wastewaters of urban communes of Khmissa (Site 1), Hannancha (Site 2) and Souk Ahras (Site 3) rejected in the Medjerda wadi of Souk Ahras region (North-East Algeria) for agricultural purposes in the far North-East of Algeria is accompanied by health and environmental risks, the evaluation of which requires physico-chemical and parasitological characterization. Biweekly samples were taken from March to August 2019 at the three studied sites wastewaters discharges. The results revealed that the waters studied are characterized by high salt contents, negative redox potential and high levels of turbidity (97.28 ± 18.12 to 111.57 ± 13.11 NTU ), suspended matter (TSS) (351.6 ± 15.52 to 397.33 ± 20.6 mg.L־1), ammonium (8.51 ± 1.94 to 11.19 ± 3.18 mg.L־1) and orthophosphates (3.69 ± 1.40 to 5.29 ± 1.78 mg.L־1), high values in BOD5 (120.62 ± 43.17 to 170.25 ± 32.34 mg.L־1of O2), and COD (286.73 ± 39.65 to 358.9 ± 32.81 mg.L־1of O2) as well as the presence of some metallic trace elements such as cobalt (Co) and cadmium (Cd). Parasitological analysis shows high contamination of these irrigation waters by helminthes eggs, which exceed widely the standards of use of waste water in agriculture. The application of Principal Component Analysis (PCA) allowed to conclude that the waters of Medjerda wadi receive urban wastewater from surrounding areas and should not be reused directly in agriculture before being subjected to a processing, in order to improve their quality by meeting the required standards.